(untitled) (International Journal of Economics Management and Social Science, 2026)
This study examines the relationship between Fiqih (Islamic jurisprudence) learning and the formation of students’ social behavior from a sociology of education perspective. Using a mixed-methods approach with 320 students from Islamic boarding schools (pesantren) in East Java, Indonesia, the research investigates how structured religious instruction shapes prosocial attitudes, interpersonal conduct, and community engagement. Quantitative data were collected through validated questionnaires employing Likert scales, while qualitative insights were gathered through in-depth interviews and classroom observations. Results demonstrate a statistically significant positive correlation (r = 0.712, p < 0.001) between the quality and intensity of Fiqih learning and the level of prosocial behavior among students. Structural equation modeling reveals that pedagogical approach, teacher credibility, and curriculum relevance mediate this relationship. The findings suggest that integrating sociological frameworks into religious education practice can enhance moral formation outcomes, contributing to the broader discourse on values-based education in pluralistic societies. Keywords: Fiqih learning; social behavior; sociology of education; Islamic education; prosocial behavior; moral formation